The incrimination of three trypanosome species in clinically affected German shepherd dogs in Sudan - Mossaad, Ehab; Satti, Rawan A.; Fadul, Abdeen; Suganuma, Keisuke; Salim, Bashir; Elamin, E. A.; Musinguzi, Simon Peter; Xuan, Xuenan; Inoue, Noboru (Parasitology research, 2017)
Canine trypanosomosisis (CT) is a common disease caused by tsetse- and non-tsetse-transmitted trypanosomes worldwide. The severity of the disease varies from acute, sub-acute to chronic with non-specific clinical signs. Here, we attempt in a cross-sectional study to assess the current situation of CT and the role of dogs in transmitting trypanosomes to other domesticated animals. The study was carried out during July 2016 on 50 caged German shepherd dogs in Khartoum State to investigate the prevalence of dog trypanosomosis using both serological (CATT/Trypanosoma evansi) and molecular (KIN-PCR, RoTat1.2 VSG-PCR and TviCatL-PCR) tests to detect possible trypanosome infections. CATT/T. evansi detected antibodies against T. evansi in 15 (30%) dogs, while parasite DNA was detected in 17 (34%) dogs by RoTat1.2 PCR. In contrast, a KIN-PCR detected the subgenus Trypanozoon, Trypanosoma congolense savannah, T. congolense Kenya and T. vivax in 36 (72%), 3 (6%), 1 (2%), and 2 (4%) dogs, respectively. However, a species-specific PCR for Trypanosoma vivax was detected 7 (14%) positive cases. We concluded that CT was caused by at least three species of trypanosomes, namely T. evansi, T. vivax and T. congolense. Trypanozoon other than T. evansi could not be ruled out since other tsetse-transmitted trypanosomes have also been detected and species-specific PCRs were not used. This study illustrates that dogs play an important role in the transmission dynamic and the epidemiology of the above mentioned trypanosome species.
Keywords: Dog; Trypanosoma evansi; Trypanosoma vivax; Trypanosoma congolense